Dynamic changes and mechanisms of organic acids during black tea manufacturing process. (February 2022) - Yu, Fei; Chen, Cong; Chen, Shuna; Wang, Kaixi; Huang, Haitao; Wu, Yuanyuan; He, Puming; Tu, Youying; Li, Bo
Abstract: Sourness usually reduces the sensory quality of black tea, and organic acids are considered as one of major contributors. A UPLC-MRM-MS method was successfully developed to analyze organic acids during the processing of black tea made of "Yingshuang" tea variety. The contents of quinic acid and citric acid increased first and then decreased during withering, but didn't significantly changed after the whole processing. Malic acid content obviously dropped in early withering, and then stayed at low level. These three acids at withering stage were regulated by quinate dehydrogenase (QDH), citrate synthase (CS), phosphoenolpyruvate carboxylase (PEPC) and malic enzyme (ME). Gallic acid sharply increased after rolling, resulted from the hydrolysis of epigallocatechin gallate (EGCG) by endogenous tannase. This work revealed the dynamic changes and regulatory mechanisms of organic acids during the black tea manufacturing process, which is helpful to improve the processing technology and quality of black tea. Graphical abstract: Image 1 Highlights: A UPLC-MRM-MS method was developed to analyze organic acids in black tea. The contents of quinic acid, citric acid and malic acid changed during withering. The three acids were regulated by four enzymes including QDH, CS, PEPC and ME. Gallic acid increased after rolling, due to the hydrolysis of EGCG by tannase. Fermentation is not the major processing step for organic acid accumulation.